Enhanced decentralized PI control for fluidized bed combustor via advanced disturbance observer. (September 2015) - Sun, Li; Li, Donghai; Lee, Kwang Y.
Abstract: Motivation of this paper is to propose an engineering friendly control strategy to handle the various difficulties in fluidized bed combustor (FBC). The control objectives of FBC and the difficulties arisen from nonlinear dynamics, frequent disturbances and strong coupling are first formulated. The capability of the disturbance observer (DOB) to handle the nonlinearity and disturbances is analyzed and the decoupling effect of DOB is revealed in terms of equivalent transfer function. For the power loop, a robust loop shaping design method is proposed to balance the performance and robustness of DOB. For the temperature loop, the DOB filter is designed based on H∞ optimization. Abilities of DOB are confirmed by numerical simulations. A water tank experiment is designed to show the simplicity of implementing DOB in an industrial Distributed Control System. Finally, a global simulation on the FBC process demonstrates that, compared with the conventional PI scheme, the DOB-enhanced PI strategy achieves overall improvement and can even be comparable with the complex Model Predictive Control in some aspects. Highlights: Difficulties in FBC control are treated within a unified framework of DOB. The equivalence of inverted decoupling and DOB is revealed for the first time. Advanced DOB design is proposed to accommodate time delay and NMP characteristics. The experiment shows that the DOB can be conveniently implemented in DCS.